Characterization of a zeolite-templated carbon by electrochemical quartz crystal microbalance and in situ Raman spectroscopy. (August 2015) - Leyva-García, S.; Nueangnoraj, K.; Lozano-Castelló, D.; Nishihara, H.; Kyotani, T.; Morallón, E.; Cazorla-Amorós, D.
Abstract: Electrochemical quartz crystal microbalance was used to monitor the mass changes during the electrochemical characterization of a zeolite-templated carbon (ZTC) in 1 M H2 SO4 medium. Under electrochemical oxidation conditions, a high anodic current and a net mass increase were recorded, resulting in the increase of the specific capacitance owing to the contribution of the pseudocapacitance, mainly derived from the hydroquinone–quinone redox couple. Under more severe electrochemical conditions, a net mass loss was observed, revealing that electrochemical gasification took place. Surface chemistry, before and after the electrochemical treatments, was analyzed through temperature programmed desorption experiments. Furthermore, in situ Raman spectroscopy was used to further characterize the structural changes produced in ZTC under the electrochemical conditions applied, supporting that high potential values produce the electrochemical oxidation and degradation of the carbon material.